The hidden burden: Impostor syndrome among women of color in STEM education - Guerin, Anissa (American Journal of STEM Education, 2026)
Impostor syndrome presents a persistent barrier to belonging, confidence, and persistence among women of color in STEM education. While commonly framed as an individual psychological struggle, impostor feelings are shaped by intersecting racial and gender identities and reinforced by institutional climates marked by underrepresentation, microaggressions, and exclusionary practices. This conceptual review synthesizes recent scholarship to examine how structural inequities within STEM environments contribute to chronic self-doubt, emotional strain, and constrained academic and career pathways. Guided by intersectionality and critical consciousness, the review reframes impostor syndrome as a systemic and educational issue rather than a personal deficit. The analysis highlights documented psychological and educational consequences and identifies institutional leverage points, including culturally responsive mentorship and identity-affirming practices, to promote equity and persistence for women of color in STEM.